A Study on Curing between Shellac and Polyamide Resin by Dielectric Measurements - Prasad, K.M.; Jha, P.C. (Asian Journal of Chemistry, 2010)
A study was done to investigate the curing between shellac and polyamide resin, in solution stage by the measurement of dissipation factor (tan δ ) at 100 kHz. It was found that the measurement of dissipation factor with time can be conveniently used for the determination of cure time of shellac polyamide resin blend.